Konstruksi Identitas Penggemar Musik Metal: Studi Kasus pada Kelompok Pasukan Babi Neraka - Allanm Nugroho, Mochammad; Junaedi, Fajar (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2025)
This study explores the construction of communication identity within the “Pasukan Babi Neraka” metal music fan community in Surakarta through a qualitative case study using ethnographic methods. Data were collected via participant observation and in-depth interviews with five active members. The analysis applies Michael Hecht’s Communication Theory of Identity (CTI), which comprises four layers: personal, enactment, relational, and communal. The findings reveal that personal identity is shaped by emotional connections to metal music and individual meaning-making. The enactment layer is reflected in expressions of identity through physical attributes, social media activity, and participation in community events. The relational layer emerges from solidarity, emotional support, and interpersonal interactions that foster a sense of family. The communal layer is seen in collective actions such as charity concerts and local cultural promotions that strengthen group identity. These layers interact dynamically through interpenetration, demonstrating that metalhead identity is not monolithic but fluid and responsive to social contexts. This study affirms that metal fan communities are not deviant subcultures, but rather spaces of meaningful cultural expression, social solidarity, and resistance to stigma. Metal music and popular culture function as central mediums in constructing complex identities across both digital and physical spaces.